The first thousand years : a global history of Christianity - Wilken, Robert Louis, 1936- (New Haven : Yale University Press, 2012)
"How did a community that was largely invisible in the first two centuries of its existence go on to remake the civilizations it inhabited, culturally, politically, and intellectually? Beginning with the life of Jesus, Robert Louis Wilken narrates the dramatic spread and development of Christianity over the first thousand years of its history. Moving through the formation of early institutions, practices, and beliefs to the transformations of the Roman world after the conversion of Constantine, he sheds new light on the subsequent stories of Christianity in the Latin West, the Byzantine and Slavic East, the Middle East, and Central Asia. Through a selected narration of particularly noteworthy persons and events, Wilken demonstrates how the coming of Christianity set in motion one of the most profound revolutions the world has known. This is not a story limited to the West; rather, Christian communities in Ethiopia, Nubia, Armenia, Georgia, Persia, Central Asia, India, and China shaped the course of Christian history. The rise and spread of Islam had a lasting impact on the future of Christianity, and several chapters are devoted to the early experiences of Christians under Muslim rule. Wilken reminds us that the career of Christianity is characterized by decline and attrition as well as by growth and expansion. Ten years in the making and the result of a lifetime of study, this is Robert Louis Wilken's summa, a moving, reflective, and commanding account from a scholar at the height of his powers"--
"A narrative account of the history of Christianity from its beginning to the end of the first millennium. The principal theme is the slow drama of the building of a Christian civilization. A major theme is the mission of Christians among different peoples in many regions of the ancient world: Ethiopia, Nubia, Armenia, Georgia, Persia, central Asia, India, China as well as among the Germanic peoples of northern Europe and the Slavic peoples in the Balkans and Russia. The rise and spread of Islam is integral to the story"--
Beginning in Jerusalem -- Ephesus, Rome, and Edessa : the spread of Christianity -- The making of a Christian community -- Divisions within -- Constructing a catacomb -- A learned faith : Origen of Alexandria -- Persecution : Cyprian of Carthage -- A Christian emperor : Constantine -- The Council of Nicaea and the Christian creed -- Monasticism -- A Christian Jerusalem -- Emperor Julian, the Jews, and Christians -- Bishop and Emperor : Ambrose and Theodosius -- Architecture and art -- Music and worship -- The sick, the aged, and the poor : the birth of hospitals -- The bishop of Rome as pope -- An ordered Christian society : canon law -- Augustine of Hippo -- The great controversy over Christ -- Egypt and the Copts : Nubia -- African Zion : Ethiopia -- Syriac-speaking Christians : the Church of the East -- Armenia and Georgia -- Central Asia, China, and India -- A Christian empire : Justinian -- New beginnings in the West -- Latin Christianity spreads north -- The sacking of Jerusalem : more controversy over Christ -- No God but God : the rise of Islam -- Images and the making of Byzantium -- Arabic-speaking Christians -- Christians under Islam : Egypt and North Africa -- Christians under Islam : Spain -- An emperor in the West : Charlemagne -- Christianity among the Slavs.
Includes bibliographical references and index.
Keywords: Church history -- Primitive and early church, ca. 30-600.; Church history -- Middle Ages, 600-1500.